(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2015)
This paper looks at perceptions of heritage language in two minority communities in Malaysia: the Aceh community at Kampung Aceh in Kedah; and the Portuguese-Eurasian community at the Portuguese Settlement in Malacca. The heritage languages of these communities—Acehnese and Malacca Portuguese Creole or Cristang—continue to be used within the multilingual and multi-ethnic makeup of Malaysia, where Malay is the national language and where English is also widely used, alongside other local languages such as Mandarin, Cantonese and Tamil. Based on interviews with selected respondents from these two locations, it was found that both communities regarded their heritage languages positively, and regarded their languages as an important part of their cultural heritage. The Acehnese community, despite being culturally similar to the Malays, still try to hold on to their heritage language. For the Portuguese Eurasians, their heritage language is one way to distinguish themselves as a cultural group with European and Asian roots.